Nanosilicates and molecular silicate dust species: properties and observational prospects - Bromley, Stefan T. (Frontiers in Astronomy and Space Sciences, 2024)
Silicate dust is found in a wide range of astrophysical environments. Nucleation and growth of silicate dust grains in circumstellar environments likely involves species with diameters ranging from <1 nm (molecular silicates) to a few nanometers (nanosilicates). When fully formed silicate grains with sizes ∼0.1 μm enter the interstellar medium, supernovae shockwaves cause collision-induced shattering which is predicted to redistribute a significant proportion of the silicate dust mass into a huge number of nanosilicates. This presumed population has thus far not been unambiguously confirmed by observation but is one of the main candidates for causing the anomalous microwave emission. By virtue of their extreme small size, nanosilicates and molecular silicates could exhibit significantly different properties to larger silicate grains, which could be of astrochemical and astrophysical importance. Herein, we briefly review the properties of these ultrasmall silicate dust species with a focus on insights arising from bottom-up atomistic computational modelling. Finally, we highlight how such modelling also has the unique potential to predict observationally verifiable spectral features of nanosilicates that may be detectable using the James Webb Space Telescope.